Few-femtosecond X-ray pulse generation and pulse duration control in a seeded free-electron laser - Fan, Weijie; Qi, Zheng; Feng, Chao; Zhao, Minghua (Frontiers in Physics, 2023)
With the development of ultrafast science, free-electron lasers (FELs) with ultrashort pulses have become a state-of-the-art tool in ultrafast phenomena studies. In an externally seeded FEL, the output pulse duration is usually determined both by the seed laser pulse duration and FEL amplification process, which can hardly reach the timescale of a few femtoseconds. In this study, through a simple method of changing the relative time delay and correspondingly the pulse energy of the two seed lasers employed in a seeded FEL, we demonstrated the possibility of generating few-femtosecond soft X-ray pulses and controlling the final FEL pulse durations. Based on theoretical calculations and practical experiments, we conducted a detailed study on the capabilities and limitations to this method with the parameters of the Shanghai Soft X-ray FEL Facility. Start-to-end simulations indicate that we can achieve ultrashort soft X-ray FEL pulses with the pulse duration down to 5.2 fs, and the final pulse durations can also be controlled in terms of relative time delays.